1993
DOI: 10.1159/000175883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sotalol on Arrhythmias and Exercise Tolerance in Patients with Hypertrophic Cardiomyopathy

Abstract: The effect of sotalol on exercise tolerance and incidence of arrhythmias was studied in 30 patients with hypertrophic cardiomyopathy (HCM). In this short-term, double-blind, crossover study, exercise time on sotalol (320 mg/day) was significantly longer than on placebo (10.6 ± 4.0 vs. 9.4 ± 3.6 min; p < 0.01). Sotalol eliminated supraventricular arrhythmias in 6 of 7 patients (p < 0.03) and suppressed ventricular arrhythmias in 7 of 13 patients in whom they were present on placebo (p < 0.05). Ventricular tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…There are no prospective randomised trials of medical therapy for AF in HCM and only a very small number of observational studies assessing the effect of antiarrhythmic therapy on the maintenance of SR 5 23. In this study a propensity score analysis demonstrated that β-blockers, calcium channel antagonists and disopyramide at baseline initially prevented AF for the first 2–3 years of follow-up, but their protective effect then diminished.…”
Section: Discussionmentioning
confidence: 69%
“…There are no prospective randomised trials of medical therapy for AF in HCM and only a very small number of observational studies assessing the effect of antiarrhythmic therapy on the maintenance of SR 5 23. In this study a propensity score analysis demonstrated that β-blockers, calcium channel antagonists and disopyramide at baseline initially prevented AF for the first 2–3 years of follow-up, but their protective effect then diminished.…”
Section: Discussionmentioning
confidence: 69%
“…An implantable cardioverter-defibrillator may provide added safety with QT interval-prolonging drugs. Amiodarone or disopyramide in combination with ventricular rate-controlling agents are generally preferred (11, 466). …”
Section: Specific Patient Groups and Afmentioning
confidence: 99%
“…Other studies have reported the safety of lowdose amiodarone treatment and its potential protective effect in HCM patients with ventricular arrhythmias [46,47]. Sotalol is possibly a promising alternative option to amiodarone and has often been employed empirically, although further evidence is required regarding its longterm efficacy in HCM patients [48]. New treatment modalities based on devices such as the implantable atrial defibrillator are untested in HCM [39•].…”
Section: Treatment Optionsmentioning
confidence: 99%